PERSPEKTIF PENJERAAN DALAM RANGKA KEBIJAKAN KRIMINAL PENENGGELAMAN KAPAL PENCURI IKAN - Raka Momon Saputra (Jurnal Kriminologi Indonesia, 2017)
Illegal Fishing activity which is most often occurs in the area of fisheriesmanagement Indonesia is illegal fishing by foreign vessels illegally (KIA), which comesfrom several neighboring countries. This thesis aims to determine the criminal policyof sinking fish thieves in the perspective of deterrence and designing criminal policiessinking fish thieves in order to remain able to provide a deterrent effect in the future.This study used a qualitative approach. Illegal fishing activity is mostly done by illegalforeign vessels with a ratio of 63% KIA and 37% illegal vessels Indonesia (KII). Thetype of offense are often done are not to have licensing documents and using gear not inaccordance with the authorization document. The region most IUU fishing WPP-NRI 711is includes Karimata Strait, Natuna Sea, and South China Sea. Sinking of the fish thievesthat have been implemented by the current administration is an act that is very firm andeffective. It can be seen from the decline in the level of illegal exploitation of the fishresources (approximately 30-35%). Thought deterrence deterrent according to Winters etal, 2014, that proportionality is the power of punishment proportionate to the seriousnessof the crime. Severity is the power of condemnation, as well as the speed of the judgmentis given after the crime occurred, will increasingly influence the perpetrators. Certainty ofpunishment should be a definite action was dropped and can not be avoided. Designing thecriminal policy of sinking the illegal fishing vessels, in order to provide a deterrent effectin the future is to develop as much as possible Indonesia MoU with other countries. Madethe rules clear of the MoU and then performed a declaration with neighboring countries.